KEPEMIMPINAN TRANSFORMASIONAL DALAM KONTEKS PERUBAHAN ORGANISASI DI LEMBAGA ADMINISTRASI NEGARA (TRANSFORMATIONAL LEADERSHIP IN THE CONTEXT OF ORGANIZATIONAL CHANGE IN THE NATIONAL INSTITUTE OF PUBLIC ADMINISTRATION (NIPA/LAN)) - Mariman Darto (Jurnal Borneo Administrator, 2013)
This paper aims to describe the importance of transformational leadership role in encouraging and influencing organizational change in the National Institute of Public Administration (LAN). By using data collection method through the stock-taking of various textbooks, journals and documents, as well as the observation in the past year, this paper is expected to provide an overview of how the role of transformational leadership is able to push the organizational changes. The succession of transformational leadership can be seen at least from three important indicators, namely, changing in the organizational structure, products and culture. Analysis demonstrate that change in structure and product are relatively better compared to cultural change. Therefore, LAN's still need to work hard to transform the old habits into the new habits that reflects the expectation of internal and external stakeholders, which is professionalism in performing their duties and functions in research and training and education. Thus, the key to make all of this possible is the transformational leadership which is always ready to lead the change.Keywords: Transformational Leadership, Organizational ChangeTulisan ini bertujuan untuk mendeskripsikan pentingnya peran kepemimpinan transformasional dalam mendorong dan mempengaruhi perubahan organisasi di Lembaga Administrasi Negara. Dengan menggunakan metode pengumpulan data melalui stock-taking dari berbagai textbook, jurnal dan dokumen yang ada, serta dengan melakukan observasi dalam kurun waktu setahun terakhir, tulisan ini diharapkan dapat memberikan gambaran mengenai bagaimana peran kepemimpinan transformasional mampu mendorong terjadinya perubahan organisasi. Keberhasilan ini setidaknya dapat dilihat dari tiga indikator penting yaitu perubahan struktur, produk dan kultur. Dua indikator perubahan yang pertama, yaitu struktur dan produk, relatif lebih baik jika dibandingkan dengan perubahan kultur, dimana LAN masih harus bekerja keras untuk merubah kebiasaan lama (breaking habit) yang selama ini dilakukan menjadi kebiasaan baru yang mencerminkan harapan stakeholder baik internal maupun eksternal yaitu: profesionalisme dalam menjalankan tugas dan fungsi di bidang kajian dan kediklatan. Kunci dari semuanya itu adalah kepemimpinan transformasional yang selalu siap dalam memimpin perubahan.Kata Kunci: Kepemimpinan Transformasional, Perubahan Organisasi